Advances In Hydrogen Generation Technologies - Eyvaz, Murat (IntechOpen, 2018)
Among energy sources, hydrogen gas is clean and renewable and has the potential to solve the growing energy crisis in today's society because of its high-energy density and noncarbon fuel properties. It is also used for many potential applications in nonpolluting vehicles, fuel cells, home heating systems, and aircraft. In addition, using hydrogen as an energy carrier is a long-term option to reduce carbon dioxide emissions worldwide by obtaining high-value hydrocarbons through the hydrogenation of carbon dioxide. This book presents the recent progresses and developments in water-splitting processes as well as other hydrogen generation technologies with challenges and future perspectives from the point of energy sustainability.